2013
DOI: 10.1016/j.snb.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

SiC-FET methanol sensors for process control and leakage detection

Abstract: Two types of SiC based Field Effect Transistor sensors, with Pt or Ir gate, were tested to detect methanol in the concentration range 0-1600 ppm for both process control and leak detection applications. The methanol response was investigated both with and without oxygen, since the process control might be considered as oxygen free

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…2 Several reports have so far been published on methanol sensing properties of different metal oxides, employing various nanoforms. [3][4][5][6][7][8][9][10][11][12][13][14] However, very few have focused on the selective detection of methanol vapor against the interfering species (i.e. ethanol, 2-propanol, acetone etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Several reports have so far been published on methanol sensing properties of different metal oxides, employing various nanoforms. [3][4][5][6][7][8][9][10][11][12][13][14] However, very few have focused on the selective detection of methanol vapor against the interfering species (i.e. ethanol, 2-propanol, acetone etc.).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] A scrutiny of contemporary literature reveals that methanol sensitivity as well as selectivity of different semiconducting metal oxides has been improved by adopting the following measures: (i) incorporation of partially filled d-shell metal as a dopant or a surface modifier to semiconducting oxides, 4 (ii) use of the composite structure of different metal oxides, 4 (iii) use of an organic or inorganic membrane to selectively allow the special target molecules towards the metal oxide surface, 5 (iv) depositing noble metal as a gate material for the chemical field effect transistor (Chem-FET) sensor (e.g. Pt gate SiC-FET sensor) 6 and (v) developing a sensor array combined with appropriate pattern reorganization tools tuned for favourable target species (e.g. surface acoustic wave (SAW) sensor).…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that with both gate materials for low methanol concentration, adding oxygen to the carrier gas improved the sensor sensitivity by 20% and also reduced the response/recovery time by 50%. 121 Gallium nitrate gas sensor (GaN).-Wide band gap with small activation energy is the key design parameter for the semiconductor gas sensors which void the surrounding temperature influence on the device degradation. Both SiC and GaN serves as a material to design a sensor for extreme harsh environment due to its high chemical stability and high melting point.…”
Section: Wideband Semiconductor Gas Sensormentioning
confidence: 99%